2017
DOI: 10.4274/tybd.85866
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Noise on Hospitalized Patient’s Night’s Sleep and Vital Signs in Intensive Care Unit

Abstract: ÖZ Amaç: Gürültü, istenmeyen ve rahatsızlık veren ses olarak tanımlanmaktadır. Bu çalışmada gürültünün yoğun bakım ünitesinde yatan hastaların gece uykusu ve yaşamsal bulguları üzerine etkisinin incelenmesi amaçlanmıştır. Gereç ve Yöntem: Tanımlayıcı olarak yapılan araştırmanın evrenini, Çukurova Üniversitesi Tıp Fakültesi Beyin Cerrahi Yoğun Bakım (BCYB) Ünitesi'nde yatan hastaların tamamı, örneklemini ise araştırmanın sınırlılıklarına uyan, 18 yaş üzeri ve araştırmaya katılmayı kabul eden 83 hasta oluşturmuş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…It was found that patients exposed to high noise levels had poor sleep quality. It has been shown in previous studies that noise in hospital and intensive care environments negatively affects the sleep quality of the patients [4,5,13,22]. Our study findings are in line with the literature.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was found that patients exposed to high noise levels had poor sleep quality. It has been shown in previous studies that noise in hospital and intensive care environments negatively affects the sleep quality of the patients [4,5,13,22]. Our study findings are in line with the literature.…”
Section: Discussionsupporting
confidence: 93%
“…Although there are many studies [4,5,13,22] that evaluate the noise level in the hospital environment and its effects on patients, the number of studies evaluating the noise level in HD units is limited. In the literature, it has been observed that the noise level in the dialysis unit varies between 38.2 and 67 dB(A) on weekdays between 08:00 a.m. and 11:00 p.m. and is 40.5 dB(A) on Sunday [23] and that the average noise level recorded 10 h a day for 5 days to vary between 58.2 and 67.6 dB(A) [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noise levels in ICUs have been reported to exceed average values 34 . Demir and Öztunç investigated the effect of noise on nocturnal sleep and vital signs in intensive care patients and reported a mean noise level of 52.04 ± 5.75 dB, while Terzi et al reported a mean level of 71 dB and Garrido Galindo et al a mean level of 64.00 ± 3.62 dB(A) (maximum 76.04 ± 5.73 dB, minimum 54.84 ± 2.61 dB), all above average values 10,35,36 . The WHO has reported a maximum tolerable level of 50 to 55 dB(A) 7,10 .…”
Section: Discussionmentioning
confidence: 99%